Teachers’ perceptions of Bangladeshi EFL tertiary learners’ writing challenges - Karim, Shah Mohammad Sanaul (IIUC Studies, 2022)
Writing is one of the most challenging skills for the Bangladeshi EFL tertiary learners. The learners, teachers and educators refer to the difficulty of the learners in writing different types of compositions. Among the types of compositions, paragraphs facilitate a learner to opt for bigger compositions as well as for discreet sentences. This study reports the findings about the paragraph writing problems of the Bangladeshi EFL tertiary level learners. Data were collected through questionnaire and semi-structured interviews. The questionnaires were distributed to 6 teachers of English Language and Literature at International Islamic University Chittagong, Bangladesh and semi structured interviews were conducted with two teachers teaching paragraph writing to the students. Findings from the questionnaires have revealed that the revising stage is very difficult for the learners followed by writing and planning stages. Findings from the semi-structured interviews with the teachers have corroborated the findings of the questionnaire. The findings draw attention to the different types of problems in the writings of paragraphs by the Bangladeshi EFL tertiary learners and provide implications. IIUC Studies Vol.19, December 2022: 19-52